Menjelajahi Geografi melalui Pembelajaran Berbasis Proyek: Integrasi Pengukuran dan Pemetaan dalam Pembuatan Maket - Aji Novia Prastanti (Proceedings Series on Social Sciences & Humanities, 2024)
Project-based learning has been implemented at Karangturi High School in Geography teaching for 10th-grade students, covering basic geography concepts and basic mapping materials. This project involves collaboration with the Physics subject in the measurement material. The focal point of this project is the creation of a school garden scale model, starting with direct field measurements as part of outdoor learning implementation. The dimensions of the garden are then calculated using a predetermined scale, and the garden model is constructed accordingly. This approach not only introduces basic geography concepts and basic mapping but also integrates physics concepts in measurement and scale. Through this project, students not only learn theory but also apply it directly in real-world contexts, enhancing their understanding of geography concepts and practical skills such as measurement and model making. Research findings indicate that this project-based learning in Geography is effective in improving students' understanding of basic geography concepts, basic mapping, and measurement, as well as enhancing their engagement and learning motivation. Practical implications of this research suggest that project-based learning approaches can be beneficial strategies in enhancing the effectiveness of Geography education in high schools, by integrating various subjects and encouraging active student engagement through engaging and relevant learning experiences.